Development of foldable and portable goalpost for street soccer - Muhammad Fakhrul, Hashim (2008)
The idea to create and build a portable and foldable goalpost for street soccer is come from supervisor that gives me this title and task for this project. To design and fabricated this goalpost, it must be compare with other product that maybe available in the market. First, get an idea from internet, magazine, newspaper or other from available data. Form there the information and idea to design and fabricated can be created. Whole project involves various methods such as collecting data, concept design and fabrication process. The whole project involved various method and process that usually use in engineering such as concept design, analysis process and lastly fabrication process. This final year project takes one semester to complete. This project is individual project and must be done within this semester. In this project, students must able apply all knowledge during their studies in this Diploma of Mechanical Engineering course. Overall from this project, time management and discipline is important to make sure this project goes smooth as plan and done at correct time.